Study on the rates of infection and spontaneous clearance on HCV among HIV-infected men who have sex with men in China - An, Ming-hui; Han, Xiao-xu; Liu, Jing; Wu, Hao; Chen, Xi; Lu, Lin; Xu, Jun-jie; Zhang, Min; Shang, Hong (Zhōnghuá liúxíngbìng zázhì, 2013)
The aim of this study was to understand the rates of infection and spontaneous clearance on hepatitis C virus (HCV) among HIV-infected men who have sex with men (MSM) in China. HIV-infected MSM from Shenyang, Beijing, Changsha and Kunming were selected to take the HCV antibody and HVC-RNA tests, and then classified into 'under recovery (RNA-/Ab+) ' or being chronic (RNA+/Ab+). Information on demography, CD4(+) T cell, HIV viral load and liver biochemical indicators were also collected. In 513 HIV-infected MSM, the positive rate of HCV antibody was 1.94% (10/513) and the positive rate of HVC-RNA was 0.77% (4/513). Five patients showed clearance of HVC-RNA, spontaneously. These 5 patients had low levels of both alanine transaminase (ALT) and aspartate aminotransferase (AST), and with high level of CD4(+) T cells, when compared to those who were not able to clear the HVC-RNA. Currently, the HCV infection rate was still at quite low level among the HIV-infected MSM in China. Dynamic of HIV/HCV co-infection should